2004
DOI: 10.1038/sj.ijir.3901146
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan cilexetil protects cavernous tissue in spontaneously hypertensive rats

Abstract: In previous experiments, our group demonstrated morphological changes in erectile tissue from male spontaneously hypertensive rats (SHR). The present study was performed to determine whether an angiotensin II receptor blocker could protect cavernous tissue (CT) from these structural alterations in SHR. Male SHR and Wistar-Kyoto (WKY) rats were studied during 4 months. Rats were divided into three groups: SHR (n ¼ 10), SHR with candesartan cilexetil (n ¼ 10) and WKY rats (n ¼ 10). Candesartan cilexetil 7.5 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Moreover, AT1 activation mediates an increase in RhoA/ Rho-kinase activity and a decrease in eNOS protein expression, which can be readily reversed by the AT1 antagonist losartan (Jin 2009). This effect is specifically related to Ang II, which is supported by the finding that other antihypertensive agents did not improve erectile function (Toblli et al 2004a;Mazza et al 2006). Similar findings have been demonstrated in rat models of agerelated ED (in normotensive animals), with losartan improving eNOS protein expression and erectile function (Park et al 2005a), and in diabetic ED-with improvement following valsartan administration.…”
Section: Local Renin-angiotensin Systemssupporting
confidence: 76%
“…Moreover, AT1 activation mediates an increase in RhoA/ Rho-kinase activity and a decrease in eNOS protein expression, which can be readily reversed by the AT1 antagonist losartan (Jin 2009). This effect is specifically related to Ang II, which is supported by the finding that other antihypertensive agents did not improve erectile function (Toblli et al 2004a;Mazza et al 2006). Similar findings have been demonstrated in rat models of agerelated ED (in normotensive animals), with losartan improving eNOS protein expression and erectile function (Park et al 2005a), and in diabetic ED-with improvement following valsartan administration.…”
Section: Local Renin-angiotensin Systemssupporting
confidence: 76%
“…Angiotensin II and angiotensin I (precursor of angiotensin II) cause contraction of the corpus cavernosum smooth muscle of rabbit in a dosedependent manner and the effect of angiotensin I is attenuated by captopril, an ACEi [59]. In rats, candesartan cilexetil, an angiotensin II receptor blocker has been shown to have a significant protective role against high blood pressure-related morphologic changes in vessels and cavernous spaces of the erectile tissue [60]. Becker et al [61] observed that angiotensin II plasma levels are generally elevated in the systemic and cavernous blood of patients with an organogenic etiology of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, angiotensin II (Ang II) receptor subtype AT1 seems to be important in the regulation of penile erection [11]. Recently, it has been reported that an interaction against RAS can control the remodeling process in the erectile tissue in animals with arterial hypertension [12–14].…”
Section: Introductionmentioning
confidence: 99%